Supporting community based seed potato multiplication in Ethiopia - International Livestock Research Institute (International Livestock Research Institute, 2014)
This photofilm reports from Africa RISING activities in Ethiopia to transform agricultural systems through sustainable intensification. It explains how a farmer cooperative in Endamehoni woreds organized itself to produce and distribute seed potatoes..